Misalignment of Renminbi Exchange Rate Revaluation: Estimation and Implications - Zhijun Zhao; Toshiki Kanamori (Asian Development Bank Institute (ADBI), 2005)
For the past several years, the revaluation of the renminbi has been a hot topic among policy makers and economists as well as market participants inside and outside the PRC against the background of internal and external disequilibrium of the PRC economy. Based upon the history of the exchange rate system, current arguments made by various stakeholders, and surveys of different theoretical approaches, the authors develop a two-country general equilibrium model to determine the exchange rate, taking particular account of the implications of price rigidity for the policy independence of each country. An empirical test is also introduced to identify the current degree of misalignment of the renminbi compared to its estimated equilibrium rate.
hdl:11540/4171
Keywords: 330